1, 8-cineole decreases neuropathic pain probably via a mechanism mediating P2X3 receptor in the dorsal root ganglion. (December 2018) - Zhang, Ya-ling; Liu, Yi-guo; Li, Qing; Wang, Xiang-dong; Zheng, Xiao-bo; Yang, Bao-lin; Wan, Bin; Ma, Jian-min; Liu, Zeng-xu
Abstract: 1, 8-cineole is a natural monoterpene cyclic ether present in eucalyptus and has been reported to exhibit anti-inflammatory and antioxidant effects. The therapeutic effects of 1, 8-cineole on neuropathic pain and the molecular mechanisms of its pharmacological actions remain largely unknown. In the present study, we investigated the analgesic mechanisms of orally administered 1, 8-cineole in a rat model of chronic constriction injury (CCI) and examined the drug-induced modulation of P2X3 receptor expression in dorsal root ganglia. The mechanical withdrawal threshold and thermal withdrawal latency were measured in rats to assess behavioural changes 7 and 14 days after CCI surgery. Changes in P2X3 receptor mRNA expression of L4–5 dorsal root ganglia were analysed using quantitative real-time polymerase chain reaction at the 7th and 14th postoperative day. Additionally, we examined the expression of P2X3 receptor protein in L4–5 dorsal root ganglia 7 and 14 days after surgery using immunohistochemistry and western blots. We found that 1, 8-cineole can alleviate pathological pain caused by P2X3 receptor stimulation and explored new methods for the prevention and treatment of neuropathic pain. Highlights: Established a chronic constriction injury (CCI) rat model with neuropathic pain. CCI rats were given daily 1, 8-cineole intragastrically by gastric method. 1, 8-cineole can alleviate pathological pain caused by P2X3 receptor stimulation.